Factors related to the quality of life of family cancer caregivers - Liu, Zhenya; Chen, Cancan; Hu, Yanli (Frontiers in Psychiatry, 2023)
Background Cancer caregivers directly affect patient health outcomes. To maintain the function and health of caregivers so that patients can receive efficient care, we must pay more attention to caregivers’ quality of life in the process of caring for patients. However, the factors influencing caregivers’ quality of life are complex. Aim To assess caregivers’ quality of life in the process of caring for cancer patients and to explore the factors associated with it. Design This was a descriptive correlational study. A self-report questionnaire was used to anonymously collect data from one Chinese cancer hospital. The Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-Sp-12), General Self-efficacy Scale (GSES), Positive and Negative Affect Schedule (PANAS), Connor-Davidson Resilience Scale 10 (CD-RISC-10), 24-item Caregiver Burden Inventory (CBI) and Caregiver Evaluation Questionnaire were used to measure caregivers’ spiritual well-being, self-efficacy, affective well-being, resilience, caregiver burden and quality of life. One-way analysis of variance, the Kruskal–Wallis H test and multiple regression analysis were applied to measure the factors influencing caregivers’ situations. Setting and participants A total of 315 caregivers of cancer patients were selected by convenience sampling. All participants were invited to complete the questionnaire through a one-on-one approach. Results The mean score for caregiver quality of life was 204.62 ± 36.61. After controlling for demographic factors, self-efficacy (β’ = 0.265, p < 0.01), resilience (β’ = 0.287, p < 0.01) and positive affect (β’ = 0.103, p < 0.01) were protective factors for caregivers’ quality of life. Negative affect (β’ = −0.217, p < 0.01) and caregiver burden (β’ = −0.219, p < 0.01) were negative factors. Notably, not all of these predictors can predict all dimensions of quality of life. Conclusion Caregivers’ quality of life needs to be further improved. The results of this study may provide clues to help identify factors influencing caregivers’ quality of life and implement targeted strategies to improve their quality of life.